Respuesta :

Answer:

[tex]D = \frac{25\sqrt{13}}{13}[/tex]

Step-by-step explanation:

Given

[tex]y = 4 - \frac{2}{3}x[/tex]

[tex](x_1,y_1) = (-2,-3)[/tex]

Required

Determine the distance

[tex]y = 4 - \frac{2}{3}x[/tex]

Write the above equation in standard form:

[tex]Ax + By + C = 0[/tex]

So, we have:

[tex]\frac{2}{3}x+y - 4 = 0[/tex]

By comparison:

[tex]A = \frac{2}{3}[/tex]  [tex]B = 1[/tex] and [tex]C = -4[/tex]

The distance is calculated using:

[tex]D = \frac{|Ax_1 + By_1 + C|}{\sqrt{A^2 + B^2}}[/tex]

Where:

[tex](x_1,y_1) = (-2,-3)[/tex]

[tex]A = \frac{2}{3}[/tex]  [tex]B = 1[/tex] and [tex]C = -4[/tex]

This gives:

[tex]D = \frac{|\frac{2}{3} * (-2) + 1 * (-3) - 4|}{\sqrt{(\frac{2}{3})^2 + 1^2}}[/tex]

[tex]D = \frac{|-\frac{4}{3} -3 - 4|}{\sqrt{\frac{4}{9} + 1}}[/tex]

Take LCM

[tex]D = \frac{|\frac{-4-9-12}{3}|}{\sqrt{\frac{4+9}{9}}}[/tex]

[tex]D = \frac{|\frac{-25}{3}|}{\sqrt{\frac{13}{9}}}[/tex]

[tex]D = |\frac{-25}{3}|/\sqrt{\frac{13}{9}}[/tex]

[tex]D = \frac{25}{3}/\sqrt{\frac{13}{9}}[/tex]

Split the square root

[tex]D = \frac{25}{3}/\frac{\sqrt{13}}{\sqrt{9}}[/tex]

Change / to *

[tex]D = \frac{25}{3}*\frac{\sqrt{9}}{\sqrt{13}}[/tex]

[tex]D = \frac{25}{3}*\frac{3}{\sqrt{13}}[/tex]

[tex]D = \frac{25}{\sqrt{13}}[/tex]

Rationalize

[tex]D = \frac{25}{\sqrt{13}} * \frac{\sqrt{13}}{\sqrt{13}}[/tex]

[tex]D = \frac{25\sqrt{13}}{13}[/tex]

Hence, the distance is:

[tex]D = \frac{25\sqrt{13}}{13}[/tex]

Answer:

A

Step-by-step explanation: